Strategi Aliansi Bank Nagari dalam Menghadapi Disrupsi Teknologi Fintech - Mayasari, Anggi Puspita; Pujani, Vera; Hamidi, Masyhuri (Jurnal Informatika Ekonomi Bisnis, 2023)
The purpose of this study was to determine Bank Nagari's leading business segment, the type of Fintech and the collaboration model most suitable for Bank Nagari. This type of research is a case study with a descriptive qualitative approach. Research respondents are strategists or decision makers at Bank Nagari. This study uses primary data obtained from respondents' answers in the form of filling out questionnaires and interviews, namely data obtained directly from the object of research. The data analysis technique uses the Quantitative Strategic Planning Matrix (QSPM) to select alternative strategies which include Internal Factor Evaluation (IFE) matrix analysis, External Factor Evaluation (EFE) matrix analysis, weighting, rating determination and multiplication of weights with ratings. The results showed that the value of selecting the bank's business segments, namely MSME and Commercial, was the most attractive alternative strategy or had the highest average TAS score of the other alternative strategies (5.784), the value of choosing the type of Fintech P2P Lending was the most attractive alternative strategy or had a total score The highest average TAS of the other strategic alternatives (5.310), the value of selecting the Channeling as collaboration model is the most attractive strategic alternative or has the highest average Total TAS score of the other strategic alternatives (5.199).